Malignant germ cell tumours of undescended testes: Imaging features with pathological correlation - Muttarak M. (2014)
Aim: To illustrate the imaging features of malignant germ cell tumours complicating undescended testes, emphasizing the importance of recognizing this condition and providing a correct diagnosis to facilitate appropriate management. Methods: The clinical presentation, ultrasonography (US) and computed tomography (CT) features of eight consecutive patients with malignant germ cell tumours of undescended testes were reviewed. Results: CT performed in seven patients showed well-circumscribed soft-tissue masses with inhomogeneous enhancement in all cases. US in four patients showed circumscribed masses with inhomogeneous echogenicity. On pathological examination, there were two cases of embryonal carcinoma and six cases of seminoma. All tumours showed necrosis that correlated to inhomogeneous areas on imaging. Conclusion: The radiologist has an important role as he may be the first physician to suggest the diagnosis. © 2004 The Royal College of Radiologists. Published by Elsevier Ltd. All rights reserved.